2022
DOI: 10.1111/adb.13255
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific metabolic signatures in methamphetamine addicts

Abstract: Methamphetamine (METH) is a commonly abused addictive psychostimulant, and METH-induced neurotoxic and behavioural deficits are in a sex-specific manner.However, there is lack of biomarkers to evaluate METH addiction in clinical practice, especially for gender differences. We utilized ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) to detect the serum metabolomics in METH addicts and controls, specially exploring the sex-specific metabolic alterations by METH abuse. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Moreover, women polydrug ecstasy users following ATD showed a more significant mood lowering relative to their controls than men [ 90 ]. On the contrary, among methamphetamine users, only males exhibited downregulated plasma Tryp levels compared with controls [ 96 ]. Since individuals with addiction problems have high comorbidity with other psychiatric problems, this may explain the different results mentioned above [ 44 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, women polydrug ecstasy users following ATD showed a more significant mood lowering relative to their controls than men [ 90 ]. On the contrary, among methamphetamine users, only males exhibited downregulated plasma Tryp levels compared with controls [ 96 ]. Since individuals with addiction problems have high comorbidity with other psychiatric problems, this may explain the different results mentioned above [ 44 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, acetylation of lysine plays an important regulatory role in cardiovascular disease ( 41 ). Both xanthine and inosine are involved in purine metabolism, while both purine and pyrimidine-related metabolites (e.g., xanthine base and adenosine 5´-monophosphate) are sensitive to METH addiction ( 42 ). Studies have shown that purine metabolism is also closely associated with cardiovascular disease, metabolic syndrome, and chronic kidney disease ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, acetylation of lysine plays an important regulatory role in cardiovascular disease [39]. Both xanthine and inosine are involved in purine metabolism, while both purine and pyrimidine-related metabolites (e.g., xanthine base and adenosine 5'-monophosphate) are sensitive to METH addiction [40]. Studies have shown that purine metabolism is also closely associated with cardiovascular disease, metabolic syndrome, and chronic kidney disease [41].…”
Section: Discussionmentioning
confidence: 99%